Mapping of ethnographic patterns of Kadazan Dusun community in Tambunan, Sabah using Geographic Information System (GIS) - Kong, Teck Sieng; Oliver Valentine Eboy; Jacqueline Pugh-Kitingan (BIMP-EAGA Unit for Tourism Development (BE-UTD), 2018)
In this decade, the preservation of traditional heritage in the Kadazan Dusun community is an important step that must be emphasized in order for future generations to know and practice their ancestral cultures. The reason is that the Kadazan Dusun community has a unique diversity of legacy tradition. Additionally, more and more countries in the world make the legacy a key component of tourism development. Therefore, it would be a loss to the community as well as the country if the tradition's heritage is extinct from practicing. Currently, the Geographic Information System (GIS) has been introduced in preserving the traditional heritage because of its effectiveness in producing ethnographic maps. This study has mapped the ethnographic area of the Kadazan Dusun community and uses the GIS application to identify the ethnographic pattern of the community. Data from research projects in 2011 was used in this study. The result of this study shows the level of density of ethnographic patterns of the Kadazan Dusun community in Tambunan. The findings of this study provide exposure to the community, especially the Kadazan Dusun in respect of areas with high ethnographic density in Tambunan, thus promoting the area as a Cultural and Heritage Tourism site and also developing knowledge in the field of ethnographic mapping.